C56 THE IMPACT OF STATIN THERAPY ON THE PROGNOSIS OF PATIENTS DISCHARGED AFTER ACUTE CORONARY SYNDROME: A SUBANALYSIS OF THE APULIA PONTE ACS STUDY. (18th May 2022) - Basso, P; Locuratolo, N; Carrata, F; De Laura, D; Cavallari, D; Rutigliano, S; Trotta, F; Basile, M; Scicchitano, P; Nalin, I; Paolillo, C; Caldarola, P
Abstract: Background: The administration of statin therapy in patients who suffered from acute coronary syndrome (ACS) is fundamental in order to avoid recurrences and adverse cardiovascular events. The long–term adherence and persistence on statin therapy is challenging. The aim of this study was to evaluate the prognostic impact of a dedicated follow–up outpatient program for patients who were discharged with the diagnosis of ACS on adherence and persistence on statin therapy. Methods: This was a subanalysis of the PONTE ACS study. The PONTE ACS study is a prospective, longitudinal, cohort study which enrolled patients who were discharged from HUB centres of ASL BARI after coronary revascularization and/or ACS. They underwent clinical evaluation at 30 days, 3, 6 and 1 year–follow–up. The data were collected after including the data in the electronic medical record of the PONTE ACS study. Anthropometric, clinical and pharmacological parameters, instrumental and laboratory examinations were included. The following endpoints were considered: all cause death, ACS recurrence/cardiac ischemia/angina, restenosis/intrastent thrombosis, stroke/transient ischemic attack (TIA), heart failure, all–cause bleeding. Results: We enrolled 2476 patients (mean age: 67.2±12.0 years). At 1–year follow–up optimal medical therapy was reached in most of patients: 84.1% were on beta–blockers, 63.1% on ACEi/sartans, 92.1% on dual antiplatelet therapy, 99.5% on statins, 16.1% on ezetimibe, and 9.9% on PCSK9 inhibitors. At multivariate regression analysis, heart rate, baseline creatinine values, and statin therapy were independent predictors of the composite endpoint all cause death, ACS recurrence/cardiac ischemia/angina, restenosis/intrastent thrombosis, while heart rate and statin therapy remained predictors of the composite endpoint death, ACS recurrence/cardiac ischemia/angina, restenosis/intrastent thrombosis, stroke/transient ischemic attack (TIA), heart failure (Figure 1 ). Conclusions: Statin therapy confirmed their therapeutic role in secondary cardiovascular prevention protocols. The need for continuing long–term statin therapy after ACS is fundamental in order to ameliorate the prognosis of patients.